A review on utilization of recycled concrete aggregates (RCA) and ceramic fines in mortar application. (2023) - Garg, N.; Shrivastava, S.
Abstract: Recently, the construction industry has greatly focused on using sustainable products during construction. Cement, coarse aggregates, and river sand are the primary consumables during any building construction. This study conducts a systematic and extensive literature analysis of numerous publications published over 20 years from 2003 to 2022. The impacts of integrating recycled concrete aggregates (RCA) and Ceramic waste are studied for both the rendering and masonry mortar. The various properties of mortar, such as its fresh state properties, mechanical and physical properties and durability-related behaviour, are analysed. The significant findings suggests that increasing the content of RCA as natural river sand replacement reduces the mechanical performance as well as the durability properties of the mortars. However, the durability and mechanical features of the mortars are improved when ceramic fines from diverse sources are included as a partial replacement for natural river sand. The study concludes that the RCA can be used up to 20–25 % and ceramic fines up to 40 %. This review highlights the prospect and potential of such construction industry wastes in mortar applications.